Oxidative stress and DNA damage in a long-term hexavalent chromium-exposed population in North China: a cross-sectional study. Issue 6 (27th June 2018) - Xu, Jing; Zhao, Meiduo; Pei, Lu; Zhang, Ruiming; Liu, Xiaolin; Wei, Lanping; Yang, Mingan; Xu, Qun
Abstract : Objective: The International Agency for Research on Cancer classifies hexavalent chromium (Cr(VI)) as a human carcinogen. As reported, cancer mortality was higher in Cr(VI)-contaminated areas. Scientists have recommended studying its health impact on people living in contaminated areas. This study aims to evaluate the health risk for people living in Cr(VI)-contaminated areas. Design: We conducted a cross-sectional study in rural areas of north-eastern China. Malondialdehyde (MDA), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT) were used as oxidative stress parameters, and 8-hydroxy-2 deoxyguanosine (8-OHdG) as a DNA damage biomarker. We collected information on demographics, lifestyles and length of residence from all participants using a questionnaire. Biological specimens and environmental media samples were collected on the same day as the survey was done. We used t-test, χ 2 test, Wilcoxon rank-sum test and multivariate linear regression analysis. Participants: The study included 319 participants exposed to Cr(VI) and 307 unexposed participants, with 447 women and 179 men. These participants met the following criteria: (1) living in the areas for more than 10 years; (2) age older than 18 years; and (3) without occupational chromium exposure. Results: Our study revealed that serum concentration of MDA (p<0.001), serum activities of CAT (p<0.001) and GSH-Px (p<0.001), as well as urine concentration of 8-OHdG (p=0.008) in the exposed group were significantly higher than those in the unexposed group. However, serum SOD activity was significantly lower in the exposed group, compared with that in the unexposed group (p<0.001). Cr(VI) exposure and smoking have an interaction effect on GSH-Px activity (p<0.05). Cr(VI) exposure and alcohol drinking also have an interaction effect on GSH-Px activity (p<0.05). Longer residence in the exposed areas increased the oxidative levels (p<0.05). Conclusions: The findings of this study showed elevated oxidative stress and DNA damage in people exposed to Cr(VI).